Dressing for Partial Thickness Burn Using Microbial Cellulose and Transparent Film Dressing : A Comparative Study - Djaprie, Shelly M; Wardhana, Aditya (Lingkar Studi Bedah Plastik Foundation, 2013)
Background: Wound dressing aims are to create moist and warm condition to accelerate wound healing, decrease level of pain, collects of exudate, decrease the need of dressing changes, cost effectiveness and protection from bacterial contamination. Microbial cellulose creates a moist environment and strong adhesion to the wound to prevent bacterial contamination and protects from temperature changes. Meanwhile transparent film dressing has advantages such as easy to evaluate, rapid rate of epithelialization and provides high comfort for patients. This study aims to evaluate the efficacy of microbial cellulose dressing compare to transparent film dressing as control, in the treatment of partial thickness burn. Method: We perform a single blind randomized clinical trial study. All patients with partial thickness burn with total body surface less than 20% area burns at any age presenting to our burn unit will be included in the study. They were dressed using microbial cellulose and transparent film as control. Result: The epithelialization rate of patients treated by microbial cellulose was significantly faster and less pain, especially in day 3 and 10 (p=0,000) than those treated with transparent dressing. This study showed patient using microbial cellulose no need to change dressing, meanwhile in transparent dressing it need 2 to 3 times dressing changes and costs more money. Conclusion: The use of microbial cellulose dressing is a versatile and effective dressing for partial thickness burns. This innovative material will be an alternative dressing in partial-thickness burn wounds.